53 High-fidelity simulation for postgraduate summative assessment. (17th November 2016) - Butler, Clare
Abstract : Simulated learning has existed in health care education in many forms for a number of decades, and has been a core pedagogical approach in higher education for many years. It is only recently however, that simulation has been used as a summative assessment modality. A newly developed postgraduate module entitled 'Care of the Deteriorating or Acutely Unwell Adult' commenced in September 2015. The module aim is to enhance the students' assessment skills and problem solving, enabling them to recognise and manage deteriorating or acutely unwell patients, exercising both technical and non-technical skills. The summative assessment comprised a simulated scenario with viva voce. Scenarios were developed and appraised for accuracy and evidence base; then piloted by the module team. They were then further reviewed in order to achieve validity and reliability and represent real life situations with the greatest precision. For the assessment, students were briefed with a short patient history and presenting problem then immersed in the situation. Students were expected to respond appropriately as the scenario of a deteriorating or acutely unwell adult (using a high-fidelity manikin) unfolded, applying relevant evidence-based assessment frameworks. In addition students were required to answer questions to further assess their underpinning knowledge, management plan and decision making. There is plethora of published literature exploring simulation as an effective learning strategy, with some evidence supporting the use of simulation for formal assessment (Ryall et al, 2016, Aldridge 2012, Holmboe et al, 2011). The use of high-fidelity simulation as a summative assessment method however, remains relatively rare. This poster will present the use of high-fidelity simulation for summative assessment at postgraduate level, sharing the experiences and challenges of developing scenarios and the assessment process. References: Aldridge M. Defining and exploring clinical skills and simulation-based education. In: Aldridge M, Wanless S (eds) Developing Healthcare Skills Through Simulation. London: Sage Publications, 2012. Holmboe E, Rizzolo M, Sachdeva A, Rosenberg M and Ziv A. Simulation-based assessment and the regulation of healthcare professionals. Simulation in Healthcare 2011;6 (7):S58–62. Ryall T, Judd B, Gordon C. Simulation-based assessments in health professional education: a systematic review. J Multidiscip Healthc 2016;9 :69–82.